- Thread starter
- #1

- Thread starter Vi Nguyen
- Start date

- Thread starter
- #1

- Moderator
- #2

- Feb 5, 2013

- 1,382

\(\displaystyle \ln\left(e^{-1}\right)=\ln(c)\)

\(\displaystyle -1=\ln(c)\)

\(\displaystyle -1=\ln(c)\)

- Thread starter
- #3

- Jan 29, 2012

- 1,151

You have posted a number of logarithm problems without, apparently, know what a "logarithm" **is**! If you are not taking a class that involves logarithms, where are you getting these problems?

$y= a^x$ is equivalent to $log_a(y)= x$.

$y= a^x$ is equivalent to $log_a(y)= x$.

Last edited: